The Effect of Internet Technology on Women’s Decision to Work at Home - Neny Aditina; Lilik Sugiharti (Jurnal Economia, 2019)
Abstract: This study aims to analyze the effect of internet technology and social demographic variables on women's decisions to work at home. Using National Labor Force Survey (Sakernas) conducted in February 2018, this study observed working women aged 15 years and over, which amounts to 36.378 observations. The model in this research is using logistic regression. The result shows that women who use the internet for primary jobs are more likely to work at home than those who do not use the internet. This study argued that internet supports flexible work for women. In general, internet technology is used for communication with consumers and promotional needs. Further analysis suggests that a policy is needed to improve communication infrastructure in rural areas as well as internet use to develop brand and transaction effectiveness. The younger woman, highly educated, experienced in training and living in rural areas are more likely to prefer working at home. Keywords: Internet Technology, Work at Home, Women Work.Pengaruh Teknologi Internet Terhadap Keputusan Perempuan untuk Bekerja di RumahAbstrak: Penelitian ini bertujuan untuk melihat peranan variabel teknologi internet dan variabel karakteristik sosial demografi terhadap keputusan perempuan untuk memilih bekerja di rumah. Data yang digunakan bersumber dari Survei Angkatan Kerja Nasional (Sakernas) Februari 2018, unit analisisnya adalah perempuan berumur 15 tahun ke atas yang berstatus bekerja dengan observasi berjumlah 36.378. Metode yang digunakan adalah analisis regresi logistik. Hasil penelitian menunjukkan bahwa perempuan yang memanfaatkan teknologi internet pada pekerjaan utama lebih berpeluang untuk bekerja di rumah dibandingkan dengan perempuan yang tidak menggunakan internet. Penelitian ini menyatakan bahwa internet mendukung terciptanya pekerjaan yang sifatnya fleksibel untuk perempuan. Secara umum teknologi internet digunakan untuk komunikasi dengan konsumen dan promosi. Peluang perempuan umur 15 tahun ke atas akan semakin besar untuk bekerja di rumah jika: berumur 15-24 tahun dan berumur 25-39 tahun; berstatus tidak kawin; berpendidikan tinggi (SMA ke atas); pernah mengikuti pelatihan kerja; dan tinggal di perdesaan. Kata kunci: Teknologi Internet, Bekerja di Rumah, Perempuan Bekerja.